RNA Sequencing of Creatine Transporter (SLC6A8) Deficient Fibroblasts Reveals Impairment of the Extracellular Matrix. Issue 9 (15th July 2014) - Nota, Benjamin; Ndika, Joseph D. T.; van de Kamp, Jiddeke M.; Kanhai, Warsha A.; van Dooren, Silvy J. M.; van de Wiel, Mark A.; Pals, Gerard; Salomons, Gajja S.
<x xml:space="preserve">Abstract</x> The most common cause of cerebral creatine syndromes is caused by mutations in the creatine transporter (SLC6A8), and no effective treatment is available yet. We performed RNA sequencing to investigate the molecular pathophysiology of this disorder, using fibroblast cells derived from eight unrelated individuals with SLC6A8 deficiency. Especially the expression of genes encoding components of the extracellular matrix and cytoskeleton altered due to SLC6A8 deficiency, and suggests an important role for creatine in the structural development and maintenance of cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>